Factors Driving Vocational College Students’ Selection of the Cosmetology Field - PELET, FHATIHAH; Hamid, Hashima (Research and Innovation in Technical and Vocational Education and Training, 2024)
This descriptive study aims to identify the factors that drive the selection of vocational college students towards the field of cosmetics based on four factors namely interest, peers, and family. The study sample consisted of 92 cosmetology certificate students from two vocational colleges in Kuala Lumpur. A set of questionnaires was used as an instrument for this study. The reliability value of the questionnaire items from the pilot study is 0.773. The results of this study were analyzed using Statistical Package for Social Science (SPSS) Window version 27.0 to obtain frequency, percentage, and mean. The findings of the study show that the highest mean value is the interest factor with a value of (4.26), while the value of the family factor is (3.80) and the value of the peer factor is (3.42). Several suggestions are made to enable further research to be done.